PENDIDIKAN MULTIKULTURAL BAGI MASYARAKAT INDONESIA YANG MAJEMUK - Kamal, Muhiddinur (AT-TALIM, 2013)
The diversity of Indonesia is a national asset which has long been considered by the founders of this nation.  It is thought that being diversity is not a barrier to realize the unity of the Republic of Indonesia.  However, the current state of our nation building indicates that such a spirit has declined as conflicts among the tribes lead to unlawful acts which raise the issues of tribes, tradition or race, and religion.  Education as a tool to resolve problems either as a state or a nation.  As a multicultural country, Indonesia is striving to horizontal conflict which may break the unity.  Multicultural education is, therefore, expected to be able to resolve the national conflicts.Copyright © 2013 by Al-Talim All right reservedDOI: 10.15548/jt.v20i3.42